مدى تطبيق منافع الموظفين كمعيار محاسبي دولي في القطاع العام بالجزائر - بوصبيع العايش, حسام; خلوط, فارس; نغموش صالح, امير (University of eloued جامعة الوادي, 2018)
تهدف هذه الدراسة مدى تأثير منافع الموظفين كمعيار دولي في القطاع العام بالجزائر ولتحقيق هذه الدراسة استخدمنا الاستبانة كأداة بحث واستخدمنا المنهج الوصفي والمنهج التحليلي . ولقد توصلت الدراسة الى النتائج التالية: 1- تقوم المؤسسات العمومية بتزويد الجهات المستفيدة بكافة المستجدات والقوائم المالية التي يتم تطبيقها في المعايير المحاسبة للقطاع العام. 2- ارتكاز النظام العمومي على تطبيق المعايير المحاسبية الدولية لقطاع العام يعتبر من متطلبات تطويره. 3- تقديم منافع نهاية الخدمة نتيجة لعرض يقدم لتشجيع ترك العمل الاختياري. The objective of this study is to assess the impact of employee benefits as an international standard in the public sector in Algeria, and to achieve this study, we used the questionnaire as a research tool and used the descriptive analytical method The study reached the following results: 1. Public institutions shall provide beneficiaries with all updates and financial statements that are applied in the public sector accounting standards. 2 - The adoption of the government system on the application of international accounting standards for the public sector is a requirement for its development 3. Provision of end of service benefits as a result of an offer to encourage voluntary leave.
مذكرة ماستر محاسبة
Keywords: القطاع العام، معايير المحاسبة في القطاع العام، منافع الموظفين.; Public sector, public sector accounting standards, employee benefits